Purchasing decision using mediation of trust in product quality and brand image - Finny Ligery, Suharto,; Yuliansyah Yuliansyah, Abdulrahman I Al Shikhy, (Opción, 2019)
The aim of the study is to investigate the measurement of purchasing decision using mediation of trust in product quality and brand image. This study uses the method of quantitative approach with survey. As a result, the decision to purchase is affected by product quality and by brand image. Trust in a brand forms when the product quality and the image of the product separately fulfil the needs of the consumer. In conclusion, product quality, brand image, and trust separately influence the decision taken by a consumer at the moment of purchase.